Pengaruh Return on Asset dan Debt to Equity Ratio Serta Firm Size Terhadap Nilai Perusahaan pada Perusahaan Farmasi yang Terdapat di Bursa Efek Indonesia - Rizki Yuliana; F Defung; Irsan Tricahyadinata (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
The purpose of this research is to test, know and explain the effect of Return on Assets, Debt to Equity Ratio, and Firm Size against Price to Book Value. The independent variables used in this research are Return on Assets, Debt to Equity Ratio, and Firm Size, while the dependent variable in this research is Price to Book Value. The population in this research is Pharmaceutical Company which listed in Indonesian Stock Exchange for period 2012-2016.  The sample in this research are 7 companies. Sampling technique used in this research is Purposive sampling technique (purposive sampling). The results of this study indicate that the variables Return on Assets, Debt to Equity Ratio, and Firm Size simultaneously have a significant influence on the Price to Book Value by showing that the value of F arithmetic of 7.654 F table of 2.67 with the significance level is less than 0.05 ie 0.000. While the results of this study showed partially that the variables Return on Assets, Debt to Equity Ratio, and Firm Size has a significant influence Price to Book Value